2022
DOI: 10.1186/s12935-022-02449-6
|View full text |Cite
|
Sign up to set email alerts
|

The functions and prognostic value of Krüppel‐like factors in breast cancer

Abstract: Background Krüppel‐like factors (KLFs) are zinc finger proteins which participate in transcriptional gene regulation. Although increasing evidence indicate that KLFs are involved in carcinogenesis and progression, its clinical significance and biological function in breast cancer are still limited. Methods We investigated all the expression of KLFs (KLF1-18) at transcriptional levels by using Oncomine and Gene Expression Profiling Interactive Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
1
15
1
Order By: Relevance
“…KM plotter was used to investigate the correlation between miR-92a-3p and prognosis, and showed that the overexpression of miR-92a led to poor clinical outcomes (Figure S1). KLF2 overexpression was related to better prognosis in our previous study, 12 which was contrary to the result of miR-92a. The expression level of miR-92a-3p was upregulated in all breast cancer cell lines compared with normal breast cells (Figure 1c).…”
Section: Resultscontrasting
confidence: 83%
See 3 more Smart Citations
“…KM plotter was used to investigate the correlation between miR-92a-3p and prognosis, and showed that the overexpression of miR-92a led to poor clinical outcomes (Figure S1). KLF2 overexpression was related to better prognosis in our previous study, 12 which was contrary to the result of miR-92a. The expression level of miR-92a-3p was upregulated in all breast cancer cell lines compared with normal breast cells (Figure 1c).…”
Section: Resultscontrasting
confidence: 83%
“…The expression level of miR‐92a‐3p was upregulated in all breast cancer cell lines compared with normal breast cells (Figure 1c). However, KLF2 was found to be remarkably downregulated in breast cancer cell lines compared with MCF‐10A cells in our previous study 12 . Moreover, qRT‐PCR (Figure 1d) and western blot (Figure 1e) revealed that the expression level of KLF2 was significantly decreased in miR‐92a‐3p‐overexpressed MCF‐7 and T47D cell lines but increased in miR‐92a‐3p‐depleted CAL‐51 and MDA‐231 cells.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…In breast cancer, cancer stem-like cells (CSC) can alter energy metabolism to focus on the hexosamine biosynthesis pathway (HBP) to permit increased cell proliferation [ 100 , 101 ]. High KLF8 expression is associated with poor prognosis of breast cancer patients and was found to play a role in the HBP [ 102 , 103 ]. About 2–5% of glucose and glutamine transported into the cell enter the HBP to generate UDP-GlcNAc.…”
Section: Breast Cancermentioning
confidence: 99%